2023
DOI: 10.1038/s41598-023-31783-6
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-mediated protection against high-fat diet induced anxiety and obesity is associated with changes in the gut microbiota in female mice

Abstract: Decreased estrogens during menopause are associated with increased risk of anxiety, depression, type 2 diabetes and obesity. Similarly, depleting estrogens in rodents by ovariectomy, combined with a high-fat diet (HFD), increases anxiety and adiposity. How estrogens and diet interact to affect anxiety and metabolism is poorly understood. Mounting evidence indicates that gut microbiota influence anxiety and metabolism. Here, we investigated the effects of estradiol (E) and HFD on anxiety, metabolism, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 132 publications
1
3
1
Order By: Relevance
“…In this investigation, a significant reduction in anxiety was observed with the positive impact of treatment with probiotics and changes in lifestyle habits, such as practicing meditation, yoga, deep breathing, in reducing anxiety levels. These results are consistent with previous studies that have shown a correlation between gut health and mental health, highlighting the importance of the gut microbiota in regulating mood and emotional well-being [46][47][48].…”
Section: Discussionsupporting
confidence: 93%
“…In this investigation, a significant reduction in anxiety was observed with the positive impact of treatment with probiotics and changes in lifestyle habits, such as practicing meditation, yoga, deep breathing, in reducing anxiety levels. These results are consistent with previous studies that have shown a correlation between gut health and mental health, highlighting the importance of the gut microbiota in regulating mood and emotional well-being [46][47][48].…”
Section: Discussionsupporting
confidence: 93%
“…Gonadal hormones, such as estradiol and testosterone, play a significant role in sex differences, including protection and resistance to diet-induced obesity in female mice. 105 , 106 While our results reveal lower variance in females, indicating a limited impact of the estrous cycle on our findings, we did not track the estrus cycle across the 24-h period. Therefore, we cannot exclude the role of gonadal hormone status in the interaction between microbial circadian rhythms, diet, host gene expression, and sex differences in metabolism.…”
Section: Discussioncontrasting
confidence: 64%
“…Tenofovir disoproxil fumarate-loaded silver nanoparticles have been shown to restore hypothalamic-pituitary-gonadal axis function, normalise hormonal profiles and improve testicular function and structure to alleviate reproductive dysfunction in diabetic rats ( Olojede et al., 2022 ). Evidence that the variety and diversity of the gut flora is regulated by oestrogen ( Acharya et al., 2023 ; Song et al., 2023 ). Whereas changes in the type and number of intestinal flora are present in both type 2 diabetics and animals, and the application of probiotics to regulate intestinal flora is also a means of treating type 2 diabetes, therefore, we propose pituitary gonadal axis-microbes as a new strategy for the direction of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%